2014
DOI: 10.22495/rgcv4i4c1art1
|View full text |Cite
|
Sign up to set email alerts
|

The quality of institutions and financial development in mena countries: An empirical investigation

Abstract: This paper provides new evidence that sheds light on the influence of institutional quality on financial development using data from Middle East and North African (MENA) countries over the period of 1984-2007. To measure institutional quality we construct a yearly composite index (INST) using the International Country Risk Guide’s (ICRG). The results of both panel data and IV techniques of estimation show that the institutional quality is more relevant for banking sector than for stock market development. Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Gazdar and Cherif's (2015) latest results supported that institutional quality played an important role in the MENA's financial system. However, this role is more relevant for the banking sector than for stock market development.…”
Section: Introductionmentioning
confidence: 70%
“…Gazdar and Cherif's (2015) latest results supported that institutional quality played an important role in the MENA's financial system. However, this role is more relevant for the banking sector than for stock market development.…”
Section: Introductionmentioning
confidence: 70%
“…80.3% of the auditors sampled have reported that they have encountered financial frauds during external auditing practices. The percentage of the sampled auditors that have reported financial statement frauds during external auditing is almost equal to the number of the auditors complying with ISA 240 legislatives (78.8%) hence an indication that the use of ISA 240 tool can help to identify the fraud cases (Gazdar, & Cherif, 2014). Moreover, the number of fraud cases identified and reported as a result of compliance with the ISA 240 legislation is an enough proof that the Jordan auditors are committed to apply ISA 240 in external auditing practices (Ghazangs, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we select control of corruption, rule of law, regulatory quality, voice and accountability, political stability and government effectiveness from the World Governance Indicators database. We expect that the ratio of bank credit is higher in countries with better quality of institutions (see Huang, 2005;Baltagi et al, 2009;Law and Azman-Saini, 2012;Gazdar and Cherif, 2014). 4 While better information transparency and independence lead to a stronger banking sector, bank development might improve monetary independence and transparency of economic policies.…”
Section: Datamentioning
confidence: 99%